Quantitative assessment of acoustic Intensity in HIFU - Nie, Jian Cheng (2016)
Background and Objectives High Intensity Focused Ultrasound(HIFU) has became more and more popular and important in tumor therapy. It is so sharp that can easily remove tumors with rapid speed beyond your imagination. Actually HIFU is not a real knife but a ultrasound which is focused by transducer in vitro, converged and formed a sound field with high energy density around the tumor. It can kill the tumor on sight easily by its transient heat effect. There is not enough time to allow heat conduction to take place in surrounding normal tissue that makes HIFU win the fame of noninvasive technique. For safety's sake during the treatment, it is necessary to know exactly the parameters of acoustic field in HIFU, such as power, pressure and intensity. Due to the complexity of HIFU acoustic field, scholars have been unable thus far to give a comprehensive way to accurately detect it.